In vivo conversion of astrocytes to oligodendrocyte lineage cells using chemicals: targeting gliosis for myelin repair. (4th October 2018) - Zare, Leila; Baharvand, Hossein; Javan, Mohammad
Aim: It would be clinically ideal to target astrocytes in vivo for conversion into oligodendrocyte lineage cells to reduce astrogliosis and generate new myelinating cells.Materials & methods: Here, we prepared a GFP-labeled human astrocyte cell line, treated with epigenetic modifiers trichostatin A or 5-azacytidine and transplanted them into cuprizone-induced demyelinated mice brains. The fate of the transplanted astrocytes was studied at days 7, 14 and 28 post-transplantation.Results: GFP + astrocytes were reduced over time, whereas the GFP + oligodendrocyte lineage cells were found on days 14 and 28. Nontreated astrocytes did not convert to myelinating cells following transplantation. Cell conversion was proved in vitro by maintaining the treated cells in oligodendrocyte progenitor cell medium.Conclusion: These findings seem promising for the application of epigenetic modifiers, especially their targeted delivery to glial scars to treat demyelinating diseases.